Photoacclimation in Antarctic bottom ice algae: an experimental approach - MANGONI, OLGA; G. C. CARRADA; M. MODIGH; G. CATALANO; V. SAGGIOMO (2009)
The aim of the study was to investigate the capacity of microalgae from the extremely low light habitat of bottom ice to acclimate to different light conditions. During austral spring 1997 the bottom layer of land-fast ice in Terra Nova Bay displayed high values of microalgal biomass up to 2,400 lg Chla L-1 concentrated in a few centimetres ice layer. The algal assemblage was dominated by benthic pennate diatoms. Photoacclimation of the microalgae was addressed in terms of pigment spectra and photosynthetic parameters. Immediate and long term (minutes to days) changes in the photoprotective pigments (DD-cycle) were analysed. Severe photodamage occurred in microalgal assemblages exposed to high light. However, part of the bottom ice algal community showed a notable ability to acclimate to high irradiance levels. Changes in photosynthetic parameters preceded the sudden abrupt changes in pigment synthesis and the rapid increase in biomass and growth rates.